Textual Subversion in Memes: A Semantic-Pragmatic Sociopragmatic Triangulation of Digital Discourse - Ita Fitriana (The Doctoral Studies Program of Linguistics of Udayana University, 2025)
This study employs a semantic-pragmatic-sociopragmatic framework to analyze five Indonesian memes, exploring their role as cultural artifacts that navigate modern societal tensions. Through qualitative multimodal discourse analysis, the research examines how memes blend linguistic creativity, humor, and visual symbolism to critique issues such as academic pressure, procrastination, and cultural apathy. Key findings reveal that memes rely on semantic contrasts (e.g., literal vs. figurative meanings) to generate irony, pragmatic strategies like hyperbole and satire to subvert institutional norms, and sociopragmatic resonance to reflect collective experiences. Examples include the juxtaposition of Javanese cultural values with universal symbols (